ASSOCIATION AMONG FUNCTION-RELATED TESTS, PAIN, AND DEMOGRAPHIC DATA IN INDIVIDUALS WITH SHOULDER DISORDERS - Prasert Sakulsriprasert (2022)
Background: Function-related tests for shoulder disorders are probably related to pain and demographic data which need to be investigated. This paper aimed to study the associations among function-related tests, pain, and demographic data in individuals with shoulder disorders. Methods: The demographic data, pain by numerical rating scale (NRS), and function-related tests which are hand behind neck (HBN) and hand behind back (HBB) tests were collected. The associations were analyzed using the Spearman correlation coefficient and point-biserial correlation. Results: Five hundred sixty-six individuals with shoulder disorders participated. High significant association was reported between HBN and HBB (rs=0.780, p<0.001). Also, NRS (rs=-0.196, rs=-0.237), age (rs=-0.258, rs=-0.241), number of underlying diseases (rs=-0.161, rs=-0.171), and diabetes mellitus (DM) (rpb=-0.124, rpb=-0.143) had significant correlations with HBN and HBB tests. Conclusion: The association among HBN, HBB, NRS, age, number of underlying diseases, and DM reflected the importance of pain management and the considerations of the patient's background involving age and underlying diseases.